Environmental justice and the politics of climate change adaptation – the case of Venice. - Alba, Rossella; Klepp, Silja; Bruns, Antje (Copernicus Publications, 2020)
In this intervention, we reflect on the potential of environmental justice and climate justice approaches to reveal the politics of climate change adaptation. Taking the attempts at dealing with extreme flooding events in Venice as an example, we illustrate that different dimensions at the core of the environmental justice concept (distributive and procedural justice and justice as recognition) are helpful to analyse and to politicise climate change adaptation interventions. We call for a transformative research agenda to reconfigure interventions and expertise to more closely account for the socio-political processes and narratives shaping coastal environments and to foster multiple epistemologies. Above all, this entails strengthening the inclusion of local (environmental) knowledge, the involvement of the populations affected by interventions in adaptation planning and the open discussion of political questions and values shaping interventions.
Keywords: Umweltgerechtigkeit; Klimawandel; Klimafolgenanpassung; Hochwasserrisiko; Hochwasserschutz; Risikoabschätzung